Student Perceptions and Adaptations to Quality Assurance of Education Services During the 2019 Corona Pandemic: Persepsi Dan Adaptasi Mahasiswa Terhadap Jaminan Mutu Layanan Pendidikan Pada Masa Pandemi Corona 2019 - Anshori, Isa; Hidayah, Rima Nurul (Universitas Muhammadiyah Sidoarjo, 2021)
This study examines student perceptions of the quality assurance of education services so that they can adapt during the Covid-19 pandemic. Using qualitative research methods positivistic approach. The research subjects were determined purposively, namely 53 students of sociology. The type of data collected is quantitative and qualitative, using closed and open questionnaires with google form facilities, supported by documents. Likert scale 1-5 as a means of measuring student perceptions with positive and negative criteria. Tangible, emphaty, responsibility, reliability, and assurance are indicators of Quality Assurance Education Services. While the adaptation process, goals, integration, and efforts to maintain the continuity of the relationship are indicators of adaptation. Data analysis was done descriptively. The results of the study prove that there are 47.17% of students who have a negative perception of the quality assurance of educational services, but no one thinks that it is not good, in fact the category is good (39,62%), even very good (37,74%), the lowest is quite good (22,64%). This assessment is good because the socialization process is perfect, carried out by all campus components related to the process of internationalization of institutional character and the integration of Islamic values that are being pursued, so that students are aware of the limitations of ongoing services. This is what makes students able to adapt to online learning models and administrative processes that are taking place in the era of the covid-19 pandemic.